Digital Transformation and Export Performance : A Panel Data Analysis of International Market Penetration of Indonesian MSMEs - Ratna Tri Hardaningtyas; Sudarmiatin Sudarmiatin (Jurnal bintang manajemen, 2025)
The phenomenon of digital transformation is crucial for Indonesian Micro, Small and Medium Enterprises (SMEs) in addressing the challenges posed by international markets; however, a large number of SMEs have yet to fully utilise technological advancements. This research seeks to examine the impact of digital transformation on the export performance of Indonesian SMEs, while exploring the mediating and moderating factors that influence this relationship. The methodology employed consists of panel data analysis, utilising a sample of 100 exporting SMEs from various industry sectors over the period 2019 to 2023. The findings show that digital transformation exerts a significant positive impact on export performance, with dynamic capabilities serving as a mediator and firm size acting as a moderator. The study identifies e-commerce and business process automation as the most effective elements in improving export performance. The implications derived from this study advocate a comprehensive strategy in the digital transformation of SMEs, in addition to more targeted policy initiatives aimed at strengthening the dynamic capabilities of these firms.